Pemetaan Penelitian Terkait Implementasi IFRS 15 Tentang Pendapatan dari Kontrak dengan Pelanggan - Amardianto Arham; Doni Habibur Rahman; Firdiyawan Lisdiyanto (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2020)
This study aims to map various research results of standard implementation about Revenue from Contracts with Customers (PSAK 72 in Indonesia and IFRS 15 in other countries) in order to find out the focus of research in terms of location of research object, research topics (perceptions, impacts, and problems), and position ( pros / cons) toward this standard. This study uses a qualitative method with a bibliographic approach. The objects used in this study are 22 research articles about implementation of PSAK 72 (IFRS 15). The results of mapping analysis show that the most discussed research topic is the impact. The focus of research that uses the topic of impact and perception is the preparers of financial statements. Meanwhile, research that uses the topic of problem has provided perspective from two sides (the preparers and the users of financial statements). The results of mapping analysis show that majority of the position of the research object toward the implementation of IFRS 15 is still unclear because it shows that the position is on two sides, the pros and cons.